2019
DOI: 10.1155/2019/2168709
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Urine-Derived Stem Cells Ameliorates Erectile Function and Cavernosal Endothelial Function by Promoting Autophagy of Corpus Cavernosal Endothelial Cells in Diabetic Erectile Dysfunction Rats

Abstract: Aims. Cavernosal endothelial dysfunction is one of the factors in developing diabetic erectile dysfunction (DED), but the mechanism of cavernosal endothelial dysfunction is unclear. The present study is aimed at determining the contribution of autophagy in cavernosal endothelial dysfunction of DED rats and explaining the therapeutic effect of urine-derived stem cells (USCs). Methods. After rat corpus cavernosal vascular endothelial cells (CCECs) were isolated and cultured in vitro, CCECs were treated with adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 54 publications
(68 reference statements)
1
22
0
Order By: Relevance
“…Zhang et al[ 79 ] worked on STZ-diabetic Sprague-Dawley rats that received bilateral intracavernous injection of 1 × 10 6 USCs in 200 μL PBS-1X. The authors showed that the injection upregulated autophagic activity in the cavernosal endothelium, improving cavernosal endothelial and diabetes-induced erectile function.…”
Section: Uscs: Applicationsmentioning
confidence: 99%
“…Zhang et al[ 79 ] worked on STZ-diabetic Sprague-Dawley rats that received bilateral intracavernous injection of 1 × 10 6 USCs in 200 μL PBS-1X. The authors showed that the injection upregulated autophagic activity in the cavernosal endothelium, improving cavernosal endothelial and diabetes-induced erectile function.…”
Section: Uscs: Applicationsmentioning
confidence: 99%
“…There is evidence that the accumulation of AGEs and RAGE is associated with diabetic complications and is responsible for cavernoma endothelial dysfunction in T2DMED. 7,11 In the study, it was found that ICA II could decrease the levels of RAGE and AGEs in T2DMED rats.…”
Section: Discussionmentioning
confidence: 97%
“…Long-term disorders of glycolipid metabolism in patients with DM can cause pathological changes in the penile erectile tissue physiological functions and structure. 9,11,13 Decreased smooth muscle cell/collagen fibril proportions, endothelial dysfunction, increased apoptosis of CCSMCs and hypogonadism has been considered as the common pathological changes for T2DMED. 10,14 A long-term hyperglycemia state can accelerate the formation of HbA1c in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erectile function of rats in each group was measured by the maximum intracavernosal pressure (ICP max ) and MAP 30 days after intratunical injection as our previously described (Zhang et al., 2019). Briefly, rats ( n = 4 per groups) were first intraperitoneal injection with pentobarbital sodium (50 mg/kg).…”
Section: Methodsmentioning
confidence: 99%